Desenvolvimento de um biossensor amperométrico baseado em uricase oxidase associado com nanopartículas de platina para detecção de ácido úrico - Anunciação, Eduardo Almeida (Universidade Federal de São Carlos, 2017)
Uric acid is an endogenous substance produced from the metabolism of purines. The concentration of serum uric acid in the human body considered normal is between 0.24 - 0.52 mmol.L-1 . High levels of uric acid in the body lead to a condition known as hyperuricemia. Therefore, the monitoring of uric acid in the body is of great importance. In this work we present amperometric biosensors based on the association of the enzyme UOx with platinum nanoparticles to detect uric acid. The technique used to assemble the films that compose the biosensor was the Layer-by-Layer (LbL). Two techniques were used for the synthesis of nanoparticles for the construction of two different film architectures. In the first architecture, the nanoparticles were deposited in situ on a polyethyleneimine (PEI) and sodium polyvinyl sulfate (PVS) film - by reducing hexachloroplatinic acid hexahydrate with sodium borohydride. The bilayers composed of (PEI/UOx)n were deposited on a film containing platinum nanoparticles deposited in situ. In the second architecture, the nanoparticles were synthesized by mixing PEI solution with hexachloroplatinic acid solution and sodium borohydride solution. This solution was deposited alternating with enzymatic solution. The amperometric analyses were performed at +0.347 V potential, with successive additions of 2 mmol.L-1 of uric acid in an electrochemical cell containing phosphate buffered saline (PBS) pH 7.4. For the first architecture, the limit of detection found by the amperometric method was 5.17 µmol.L-1 with the linear detection range comprised in the range between 3.92 - 11.3 µmol.L-1 . For the second architecture, the limit of detection found by the amperometric method was 4.68 µmol.L-1 with a linear detection range between 14.18 - 55.56 µmol.L-1 . For the same architecture an using the differential pulse voltammetry method the values of limit of detection and linear detection range were 0.11 µmol.L-1 and particles / mL, respectively. The biosensors presented limits of detection close to the values found in the literature for other biosensor proving to be efficient for the detection of uric acid.
Development of a amperometric biosensor based on uricase oxidase associated with platinum nanoparticles for detection of uric acid
Keywords: Uric acid; Ácido úrico; Biosensors; Biossensores; Técnica Layer-by-Layer; Uricase; Nanopartículas de platina; Platinum nanoparticles; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA